Analisis Efisiensi Penanganan Longsoran Menggunakan DPT Borepile dan Geotextile Ditinjau dari Aspek Biaya - Ambarwati, Ananda Salsabila; Whardani, Putri Nurul Kusuma (Jurnal Civronlit Unbari, 2026)
Landslides are one of the geotechnical problems that often occur in slopes and soft soil areas, especially on roads with peat soil conditions and high traffic volumes, such as the Simpang Niam–Lubuk Kambing STA 17+070 National Road. Changes in the 2025 budget efficiency policy have resulted in the landslide mitigation method, which was originally planned to use Borepile retaining walls (DPT), being changed to a Geotextile method, thus requiring a comparative study of the cost aspects. This study aims to analyze and compare the cost effectiveness of the bored pile retaining wall and Geotextile methods at the location. The research methods include collecting technical field data, calculating the volume of work, analyzing the unit price of work (AHSP), and preparing a Budget Plan (RAB) for each alternative. The analysis results show that the total cost of work using the DPT Borepile method is IDR 7,808,047,000, while the Geotextile method is IDR 7,151,225,000. There is a cost difference of IDR 656,822,000 or about 8.4% more economical in the Geotextile method. Based on these results, the Geotextile method is considered more economically efficient and contributes to the optimization of budget utilization in landslide management projects on peatlands.